Initial Experience of Dobutamine Stress Echocardiography in Ibn Al-Bitar Hospital for Cardiac Surgery - Mohammed, Muhannad A.; Bairam, Amjad R.; Al-Kuraishi, Muthanna H.; Muhammed, Ali A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Dobutamine stress echocardiography (DSE) is a well established non invasive test for the diagnosis and risk stratification of patients with coronary artery disease. Aim of the study was to conduct a pilot study in order to establish the basis for the future routine practice of DSE in our center (Ibn Al- Bitar Hospital for Cardiac Surgery).Patients and Methods: Fifty consecutive patients who were referred from the outpatient of our center, from August 2007 to July 2008, were included. The age range was 39 – 70 years with an average of 57.18 years. Fifty-eight percent were males. Patients were enrolled in the study in accordance with the American Heart Association/ American College of Cardiology guidelines, including mainly those who are unable to exercise due to an orthopedic problem (26%) or limited functional capacity (30%). Some Patients with resting electrocardiographic changes (20%) and non diagnostic exercise test (14%) were also included as well as five patients (10%) for the assessment of myocardial viability. The baseline echocardiogram was normal in 44 % of cases. Others had resting wall motion abnormalities due to previous myocardial infarction (50%) or left bundle branch block (6%). Dobutamine was given by a syringe or an infusion pump at incremental doses (every three minutes) of 5,10,20,30, and finally 40 μg/kg/min. Atropine was needed at peak test in 36% of cases to increase the proportion of patients who reach the target heart rate.Results: The test was positive in 5 patients (10%); negative in 34(68%), non diagnostic in 2(4%), aborted due to intolerable symptoms in 3(6%) and stopped due to arrhythmias in 3(6%) patients. Side effects included chest tightness and irritability in 40%, headache in 12%, nausea and vomiting in 10%, and postural hypotension in 4%. Infrequent ventricular/atrial ectopics occurred in 13%, supraventricular tachycardia in one patient, and complex multiple ventricular ectopics in 3 patients; no incidence of sustained ventricular tachycardia or ventricular fibrillation occurred. There was no incidence of myocardial infarction or death.Conclusions: DSE is a safe and practical test provided it is used according to the recommendedprotocols. A special unit for DSE in our centre is recommended.